A Case of Eosinophilic Gastritis with Gastric Bleeding - Dedy G Sudrajat; Hasan Maulahela (The Indonesian Society for Digestive Endoscopy, 2020)
Eosinophilic gastritis is a manifestation of gastrointestinal eosinophilic disease. The clinical symptoms are not specific, similar to other gastric disease complaints. The diagnostic aproach aside from clinical manifestations is also from endoscopic and histopathological features as the gold standard. Management includes drugs and diet. In some cases with strictures and perforations, endoscopic or even surgical intervention needed. Steroid-based therapy, especially topical preparations, is still the main choice. Other alternative therapies such as immunosuppression and targeted therapy showed good results in several case reports and small-scale studies. Further research to get a better management needed, considering the prevalence of this disease is elevated.